CXCR3 chemokine receptor guides Trypanosoma cruzi-specific T-cells triggered by DNA/adenovirus ASP2 vaccine to heart tissue after challenge. - Camila Pontes Ferreira; Leonardo Moro Cariste; Barbara Ferri Moraschi; Bianca Ferrarini Zanetti; Sang Won Han; Daniel Araki Ribeiro; Alexandre Vieira Machado; Joseli Lannes-Vieira; Ricardo Tostes Gazzinelli; José Ronnie Carvalho Vasconcelos (Public Library of Science (PLoS), 2019)
CD8+ T lymphocytes play an important role in controlling infections by intracellular pathogens. Chemokines and their receptors are crucial for the migration of CD8+ T-lymphocytes, which are the main IFNγ producers and cytotoxic effectors cells. Although the participation of chemokine ligands and receptors has been largely explored in viral infection, much less is known in infection by Trypanosoma cruzi, the causative agent of Chagas disease. After T. cruzi infection, CXCR3 chemokine receptor is highly expressed on the surface of CD8+ T-lymphocytes. Here, we hypothesized that CXCR3 is a key molecule for migration of parasite-specific CD8+ T-cells towards infected tissues, where they may play their effector activities. Using a model of induction of resistance to highly susceptible A/Sn mice using an ASP2-carrying DNA/adenovirus prime-boost strategy, we showed that CXCR3 expression was upregulated on CD8+ T-cells, which selectively migrated towards its ligands CXCL9 and CXCL10. Anti-CXCR3 administration reversed the vaccine-induced resistance to T. cruzi infection in a way associated with hampered cytotoxic activity and increased proapoptotic markers on the H2KK-restricted TEWETGQI-specific CD8+ T-cells. Furthermore, CXCR3 receptor critically guided TEWETGQI-specific effector CD8+ T-cells to the infected heart tissue that express CXCL9 and CXCL10. Overall, our study pointed CXCR3 and its ligands as key molecules to drive T. cruzi-specific effector CD8+ T-cells into the infected heart tissue. The unveiling of the process driving cell migration and colonization of infected tissues by pathogen-specific effector T-cells is a crucial requirement to the development of vaccine strategies.